Association Between Skeletal Muscle Mass and Severity of Steatosis and Fibrosis in Non-alcoholic Fatty Liver Disease - Guo, Wen; Zhao, Xin; Miao, Mengyuan; Liang, Xiuru; Li, Xiaona; Qin, Pei; Lu, Jing; Zhu, Wenfang; Wu, Juan; Zhu, Chen; Xu, Nianzhen; Zhang, Qun (Frontiers in Nutrition, 2022)
Background: Sarcopenia is known to be the risk factor of nonalcoholic fatty liver disease (NAFLD). However, studies evaluating the association of skeletal muscle mass (SMM) with liver fibrosis by transient elastography are limited. Here, we investigated the association of SMM with hepatic steatosis and fibrosis assessed in Chinese adults. Methods: Patients who underwent liver ultrasonography at the Health Promotion Center of the First Affiliated Hospital of Nanjing Medical University between January 2020 to June 2021 were enrolled. We used transient elastography to evaluate the degree of hepatic fat and liver stiffness. Appendicular skeletal muscle mass was determined by bioelectrical impedance and was adjusted for body weight to derive the skeletal muscle mass index (SMI). Results: Of 3602 finally enrolled individuals, 1830 had NAFLD and 1772 did not have NAFLD. SMI gradually decreased as the severity of hepatic steatosis increased (40.47±3.94% vs 39.89±3.57% vs 39.22±3.46% vs 37.81±2.84%, P<0.001). Individuals with F3-F4 and F2 liver fibrosis groups had significantly lower SMI than individuals with F0-F1 stages (37.51±3.19% vs 38.06±3.51% vs 39.36±3.38%, P<0.001). As the SMI increased, the percentages of subjects with mild and severe NAFLD, and the percentages of subjects in F2 and F3-F4 stage were gradually decreased. SMI was independently associated with the severity of hepatic steatosis and fibrosis by logistic regression analysis. Moreover, decreased SMI was an independent risk factor for NAFLD and fibrosis.